2015
DOI: 10.1242/dev.115451
|View full text |Cite
|
Sign up to set email alerts
|

Mouse and human blastocyst-derived stem cells: vive les differences

Abstract: Lessons learned from conserved vertebrate developmental pathways have catalyzed rapid advances in pluripotent stem cell differentiation towards therapeutically relevant cell types. The most highly conserved phases of development are associated with the early patterning of the body plan -the so-called phylotypic stage. Both prior to and after this stage there is much more divergence across species. Developmental differences between human and mouse at the blastocyst and early post-implantation stages might help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 41 publications
2
96
1
1
Order By: Relevance
“…Moreover, given the level of conservation of developmental processes at the genetic level, it seems highly likely that human development will also use the same palette of molecular tools. However -not unexpectedly, given the differences in size and life span -there are a number of important differences in the development of human and mouse embryos (Rossant, 2015). Studies of human development have been very limited, due to the highly restricted accessibility to human embryos.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, given the level of conservation of developmental processes at the genetic level, it seems highly likely that human development will also use the same palette of molecular tools. However -not unexpectedly, given the differences in size and life span -there are a number of important differences in the development of human and mouse embryos (Rossant, 2015). Studies of human development have been very limited, due to the highly restricted accessibility to human embryos.…”
mentioning
confidence: 99%
“…Janet Rossant discusses key differences between early mouse and human development, and how these relate to the ability to derive different stem cell lines from these embryos (Rossant, 2015). Looking at much later stages of development, Hans-Willem Snoeck explains, using the lung as an example, why it is essential to understand human development if we are to make progress in treating disease (Snoeck, 2015).…”
mentioning
confidence: 99%
“…Both totipotent as well as pluripotent cells belong to the germline, and both states require a finely tuned temporal and spatial control [1,2] . Interestingly, the molecular regulation of pluripotency and the signal transduction pathways associated with this developmental state are not fully conserved in different mammalian species as has been shown for pluripotent cells of human and mouse origin [3,4] . Recently, marmoset monkey and mouse pluripotent cells directly isolated from embryos were also compared [5] .…”
Section: The Totipotent and Pluripotent Stages Of The Germlinementioning
confidence: 99%
“…These data suggest that the ExE is essential for proper PGC specification and development in the mouse. However, since the anatomy and morphology of the mouse and the primate embryo are fundamentally different, with a flat germ disc in primates and an egg cylinder in the mouse [4,33] , there is no direct structural counterpart of the mouse ExE in the primate embryo [34] . Recently, it was shown that the nascent (pregastrulation) amnion is the origin of PGCs in the cynomolgus monkey [13] .…”
Section: The Role Of the Amnion And The Extraembryonic Ectodermmentioning
confidence: 99%
“…Finally, studying human and chimpanzee regulatory sequences or genes in mice is not guaranteed to recapitulate their function in primates. There are important differences between embryonic development in humans compared with model organisms, including mice (Rossant, 2015), which ultimately limit these studies to investigations of small pieces of the human genome out of context.…”
Section: The Power and Limitations Of Transgenic Model Organismsmentioning
confidence: 99%